Extrema of micro-hardness in fully pearlitic compacted graphite cast iron. (2nd September 2020) - Lacaze, Jacques; Moussa, Charbel; Thebault, Yannick; Guesser, Wilson
ABSTRACT: For improving the mechanical strength of cast irons, a fully pearlitic matrix is sought by alloying with tin, copper and manganese. This applies in particular to the compacted graphite irons considered here. While average macro- and micro-hardness values were similar for the four fully pearlitic alloys under study, it was found that high copper and low tin content showed some very high maximum micro-hardness values, significantly higher than the corresponding mean. Such values may be seen as hard points in the material that would certainly impair machinability. Discussion of the reasons for these extreme values opens directions for further studies.